The importance of social media users' responses in tackling digital COVID-19 misinformation in Africa - Stewart, Ruth; Madonsela, Andile; Tshabalala, Nkululeko; Etale, Linda; Theunissen, Nicola (SAGE Publications, 2022)
Objective Digital technologies present both an opportunity and a threat for advancing public health. At a time of pandemic, social media has become a tool for the rapid spread of misinformation. Mitigating the impacts of misinformation is particularly acute across Africa, where WhatsApp and other forms of social media dominate, and where the dual threats of misinformation and COVID-19 threaten lives and livelihoods. Given the scale of the problem within Africa, we set out to understand (i) the potential harm that misinformation causes, (ii) the available evidence on how to mitigate that misinformation and (iii) how user responses to misinformation shape the potential for those mitigating strategies to reduce the risk of harm. Methods We undertook a multi-method study, combining a rapid review of the research evidence with a survey of WhatsApp users across Africa. Results We identified 87 studies for inclusion in our review and had 286 survey respondents from 17 African countries. Our findings show the considerable harms caused by public health misinformation in Africa and the lack of evidence for or against strategies to mitigate against such harms. Furthermore, they highlight how social media users’ responses to public health misinformation can mitigate and exacerbate potential harms. Understanding the ways in which social media users respond to misinformation sheds light on potential mitigation strategies. Conclusions Public health practitioners who utilise digital health approaches must not underestimate the importance of considering the role of social media in the circulation of misinformation, nor of the responses of social media users in shaping attempts to mitigate against the harms of such misinformation.